(3TQM efgGL GdhUhd Edi Yde GdCUhds - (3HQgGf GdOjf YHO Gddg Hf eMeO GdaQZGfi GdYHQis; (3GdHjVGhj , YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, fGUQ GdOjf CHh SYjO,J (B685 (3g` ? s ((3eMeO GHQGgje Hf CMeO GdYRjR GdMSjfi s)
(3ChdgG (B:s
(3GeG HYO aEf GdWdHI deG QCh eG cJHfGg ai HYV TQM GdeNJUQGJ ef eUfaGJ s
(3BNQgG (B:s
(3aLGR GdGSJZfGA ai CUhd GdOjf dcd CMO ShGA cGf eLJgOkG Ch dG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3CUhd Gdabgs